Assessment of landslide susceptibility at Canada Hill in Miri, Sarawak / Marelyn Telun Daniel - Marelyn , Telun Daniel (2020)
Landslide occurrences have become a common sight in Miri, Sarawak due to the combination of unfavourable geological conditions, abundant rainfall and anthropogenic factors which leads to infrastructural damages following prolonged rainfall. Two of the major landslide events caused the demise of two lives and several damaged houses at Kampung Lereng Bukit. Events like this may recur if the landslide hazards are not effectively managed. Numerous studies on landslide susceptibility have been performed by researchers using different approaches. This study aims to evaluate the landslide susceptibility of Canada Hill area in Miri using a heuristic approach and bivariate statistical approach which could be helpful in future planning works. Nine landslide-controlling parameters consisting of planar failure susceptibility, slope gradient, geology, elevation, distance to lineament, slope curvature, normalized difference vegetation index (NDVI), slope aspect and cut and fill were analysed in this study, with the means of Geographic Information Systems (GIS). The susceptibility maps produced from the two methods were classified into five zones of susceptibility; very low, low, moderate, high and very high. The results of the susceptibility map produced using the heuristic approach showed a 74% success rate while this is 80.8% in the case of the bivariate statistical approach. The comparison of the two susceptibility while highlighting the major planar failures showed that the landslide susceptibility map produced by the heuristic approach showed a better agreement for all the types of failure occurrences, including the major planar failures while the landslide susceptibility map produced using the bivariate statistical approach showed a better agreement for the translational and shallow rotational failures.